2016
DOI: 10.1016/j.diii.2016.10.001
|View full text |Cite|
|
Sign up to set email alerts
|

Irreversible electroporation for locally advanced pancreatic cancer

Abstract: Pancreatic adenocarcinoma is one of the solid cancers associated with the poorest prognosis; the only curative treatment remains surgical resection but in most cases, this treatment is not possible because of distant metastasis or local extension. Irreversible electroporation is a new tumor ablation technique, which provides cellular apoptosis without any thermal coagulation effect. This technique helps preserve the ducts, vessels or nerves located in the treatment area. This article reviews the current knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…More severe complications may also occur such as more severe acute pancreatitis, portal or mesenteric thrombosis, the development of a pancreatic fistula, a bile leak, perforations of the gastro-enteric tract especially at the duodenal or transverse colon level, haemorrhages especially from the superior mesenteric artery. The actual risk of death is mainly linked to duodenal perforations or severe portal thrombosis [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More severe complications may also occur such as more severe acute pancreatitis, portal or mesenteric thrombosis, the development of a pancreatic fistula, a bile leak, perforations of the gastro-enteric tract especially at the duodenal or transverse colon level, haemorrhages especially from the superior mesenteric artery. The actual risk of death is mainly linked to duodenal perforations or severe portal thrombosis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Irreversible electroporation therefore seems to have advantages over other ablative techniques, and can be preferred on those lesions near vessels or bile ducts. From the histological point of view, after IRE early changes occur in the target tissue after already 30 min, while the macroscopic changes are slower: those occur with more delay and become noticeable only in the weeks following irreversible electroporation [27][28][29]. From a practical point of view, the application of this procedure requires to be carried out under general anaesthesia with complete neuromuscular block to thereby reduce muscle contractions caused by the electrical pulses of the stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…This minimally invasive intervention also showed potential advantage in pain control after the procedure. 48 , 49 A recent initial clinical study compared pain scores in 48 patients with PC in the IRE group and cryosurgery group and found that there was no significant difference in the mean pain score (4.95 [IRE] vs versus 4.85 [cryosurgery]) and 24-hour total hydromorphone use between them. 50 In this sense, cryosurgery may be equal to IRE and better than RF on relieving pain, but a larger and multicenter analysis is needed.…”
Section: Discussionmentioning
confidence: 99%
“…While IRE has been reported historically, only recently since 2005 has IRE shown promising results in the treatment of unresectable tumors, particularly in the liver, pancreas, and prostate. 66,67 Needless to say, with the wide gamut of technologies and techniques available for ablating tumors, it takes a collaborative and clinically minded interventional radiologist to choose and apply the best treatment for their patients.…”
Section: Percutaneous Ablationsmentioning
confidence: 99%